(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
This research aims to explore the importance of financial analysis and its contribution to enhancing environmental performance evaluation by utilizing financial ratios in financial analysis and addressing environmental issues to improve and maintain the environment and performance of government units. The research problem centres on the negative impact of neglecting financial analysis of financial statements and the financial information they contain regarding environmental performance on making appropriate decisions in performance evaluation. Therefore, the researchers sought to prove the hypothesis that using financial ratios in financial analysis and comparing financial information with non-financial information enhances environmental performance evaluation procedures. The study examined the environmental reality of the Medical City Directorate under the Ministry of Health, which is considered a unit affecting the environment. It involved an analytical review of the issued reports and financial analysis of the budget execution statement. The research concluded that the government unit in question showed weak environmental performance due to insufficient attention to pollution control, affecting most environmental aspects, and failure to apply environmental laws and regulations. Key recommendations include the need to comply with environmental laws and regulations and the necessity of establishing an environmental auditing plan or program to cover all environmental activities of the directorate.